2014
DOI: 10.1002/14651858.cd003101.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal prostaglandin (PGE2 and PGF2a) for induction of labour at term

Abstract: Analysis 10.2. Comparison 10 (2.3) PGF2a vs placebo (women with an unfavourable cervix), Outcome 2 Uterine hyperstimulation with FHR changes..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(117 citation statements)
references
References 126 publications
4
103
0
10
Order By: Relevance
“…The beneficial effects of delivery of the inhibitor of the PGE2-degrading enzyme (15-PGDH) SW033291 on hematopoietic, liver, and colon regeneration are likely due to a similar augmentation of endogenous PGE2 levels (45). Notably, PGE2 and its analogs have safely been used in patients for more than a decade, for instance to induce labor (46) and to promote hematopoietic stem-cell transplantation (44). Together with our findings, these studies pave the way for its clinical use in boosting muscle repair after injury.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of delivery of the inhibitor of the PGE2-degrading enzyme (15-PGDH) SW033291 on hematopoietic, liver, and colon regeneration are likely due to a similar augmentation of endogenous PGE2 levels (45). Notably, PGE2 and its analogs have safely been used in patients for more than a decade, for instance to induce labor (46) and to promote hematopoietic stem-cell transplantation (44). Together with our findings, these studies pave the way for its clinical use in boosting muscle repair after injury.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has shown that the vaginal delivery of prostaglandins is the most effective method in labor pre-induction compared to other routes of administration [57]. When choosing prostaglandin for labor pre-induction, one should remember that these two molecules differ significantly in terms of pharmacokinetics: misoprostol has a much stronger uterotonic effect than dinoprostone and is therefore more effective in less mature cervix, e.g.…”
Section: The Use Of Prostaglandins For Labor Pre-inductionmentioning
confidence: 99%
“…Nonetheless, mechanical methods compared to prostaglandins were found to have a decreased chance of hyper stimulation and fetal heart rate modulation [4,23] . In a review from 2011 mechanical agents were found to be more successful in women with an unfavorable cervix compared to the usage of Oxytocin alone [24,25] .…”
Section: Comparison To Pharmacological Agentsmentioning
confidence: 99%